TG-FTIR study catalytic effect of inherent metal salt on biomass pyrolysis - He, L.; Hu, S.; Sun, L.; Su, S.; Jiang, L.; Song, Yuncai; Shuai, C.; Xiang, J. (Science Press, 2014)
The raw rice straw and leached with deionized water and hydrochloric acid were studied using the method of thermogravimetric(TG) coupled with Fourier transform infrared spectrometry(FTIR) to investigate the catalytic effect of inherent metal salt during biomass pyrolysis. The results indicated alkali metals promoted decomposition reaction comparing to alkaline earth metals especially Ca hindered the reaction. The releasing gas was detected online by FTIR. The main products were CO2, CO, H2O, CH4 and some volatilizable organics contained C=O and C-O-C functional groups. Compared with raw sample, the yield of CO2, CO decreased, CH4 and some volatilizable organics increased after water leaching, all product gas of acid leaching sample were remarkable less than other two samples, which were related with the different catalytic effects of alkali and alkaline earth metals.